EVALUASI TEBAL PERKERASAN BETON SEMEN DAN RENCANA ANGGARAN BIAYA PADA RUAS JALAN KM. 38 SAMBOJA KE SEPAKU - TASA, MAN (KURVA S JURNAL MAHASISWA, 2014)
Cement concrete pavement consists of Portland cement concrete slab which is located directly above the subgrade, or above the layer of granular material (subbase) situated on the land base (subgrade). Cement concrete pavement spread the load to a larger area of land to the base, so that the largest part of the strength of the pavement structure is given by the concrete slab itself. Cement concrete pavement can be a concrete slab without reinforcement, given little reinforcement, given the continuous reinforcement, prestressed concrete or fiber. Road km. 38 Samboja to Sepaku a provincial road that connects the Kutai Kartanegara regency and Penajam Paser Utara regency. This road is also a link from Balikpapan to Penajam Paser Utara or from Samarinda to Penajam Paser Utara. The existing road has a paved road, the condition of most points of damage caused by the weight of the vehicle across the road. Coupled rainfall in East Kalimantan high enough to increase the factor of higher road damage. This road should be dealt with quickly, so that the damage does not get worse, so as to provide comfort to the road users. Collecting data in the field that is the road location data, the data on average daily rate (LHR) and data documentation. Other supporting data, obtained from the relevant government institutions. While the data analysis method evaluation thick cement concrete pavement using cement concrete road pavement planning (Pd.T-14-2003) and the method of portland cement association (PCA). Calculation of the budget plan (RAB) using analytical methods K (Bina Marga). From the results of calculations can be concluded that the cement concrete pavement thickness 27 cm otherwise able to withstand the load of vehicles passing through the road km. 38 Samboja to Sepaku up to the age of the plan. The amount of a budget plan that is necessary to continue the construction of roads km. 38 Samboja to Sepaku on STA 9 + 300 s/d 12 + 000 (length 2,700 meters), is Rp. 26,409,916,000.00.